School actors navigating between implementor & arbiter - a qualitative study on the dynamics in multilingual schools' language policy - Van Raemdonck, Maxime; Tyler, Robyn; Van Avermaet, Piet; Vantieghem, Wendelien (Current issues in language planning, 2024)
Over the past two decades, heightened migration has increased linguistic diversity in schools. For schools to cope with this multilingualism, many governments impose a monolingual policy where only the language of instruction is allowed. Although many schools adopt such a policy, the classroom practices may differ since multilingual students often revert to translanguaging-as-practice. Drawing on three key conceptual language policy (LP) models (Bonacina-Pugh, 2012. Researching 'practiced language policies': Insights from conversation analysis. Language Policy, 11(3), 213-234; Johnson & Johnson, 2015. Power and agency in language policy appropriation. Language Policy, 14(3), 221-243; Ricento & Hornberger, 1996. Unpeeling the onion: Language planning and policy and the ELT professional. TESOL Quarterly, 30(3), 401-427), this study explores LP formation across macro (government), meso (school), and micro (classroom) educational levels in Flanders, Belgium. Macro-level analysis involves scrutinizing policy documents from the Educational Department of Flanders. Meso-level investigation includes policy documents from three secondary schools, compared with insights from interviews with the schools' principals and language coaches. Semi-structured interviews with teachers (n = 18) and classroom observations (n = 138 hours) provide nuanced perspectives at the micro-level. Triangulating data reveals declared, perceived, and practiced language policies at various levels. The study underscores LP's intricate nature within a multilingual educational context. Results highlight the contrast between macro-level policy straightforwardness and the complexity faced at meso- and micro-levels, where context-specific challenges arise. As schools navigate linguistic diversity, the role of language coaches becomes pivotal in creating inclusive and effective educational settings.